Increase of papers number on each edition of Jurnal Rekayasa Proses - Petrus, Himawan Tri Bayu Murti (Jurnal Rekayasa Proses, 2023)
Significant increase of awareness to share information and to contribute to the field of process engineering from both researchers and industrial engineers, has been indicated by the increase of papers submitted to the Jurnal Rekayasa Proses. To provide ample space and opportunity for all stakeholders, the Jurnal Rekayasa Proses has decided to increase the number of papers published in each edition to 15 papers, starting from volume 17(1). By increasing the number of papers per edition, we aim to promote inclusivity and interdisciplinary collaboration. We believe that breakthroughs and new perspectives will emerge at the intersection of various disciplines, which will be accommodated by the Jurnal Rekayasa Proses. Together, let us push the boundaries of knowledge, foster interdisciplinary integration, ignite collaboration, and accelerate scientific progress. We sincerely appreciate the continuous support from researchers and industrial engineers, and we eagerly look forward to the contributions of all stakeholders as we embark on this new chapter in our journal’s publication journey.